2022
DOI: 10.3389/fpsyt.2022.827480
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Reactivity in Adolescents With Nonsuicidal Self-Injury During Exposure to Self-Injury Related Cues: Electrophysiological Evidence From a Two-Choice Oddball Paradigm

Abstract: BackgroundNonsuicidal self-injury (NSSI) may be a type of addiction, that is characterized by cue reactivity. We aimed to explore the behavioral performance and neural reactivity during exposure to self-injury cues in adolescents with NSSI and major depressive disorder (MDD).MethodsEighteen MDD patients, 18 MDD patients with NSSI, and 19 healthy controls (HC) were recruited to perform a two-choice oddball paradigm. All subjects were 12–18 years old. Neutral cues and self-injury related cues separately served a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
(71 reference statements)
2
6
0
Order By: Relevance
“…This study found that compared with HC group, NSSI group had significantly longer N2, P3a, and P3b latency and significantly lower P3a and P3b amplitude, indicating that patients with depression had lower brain nerve excitability and cognitive speed, suggesting that NSSI group may have cognitive impairment. This is consistent with previous study, as Zhou et al (2022) used oddball paradigm to compare the differences of P3b components among NSSI + MDD, MDD and HC groups. Leone et al (2021) used laser evoked potential as an index to study the suicide risk of NSSI adolescents suggest that the amplitude of N2 component in NSSI patients is reduced, which is different from our study, may be due to different experimental paradigms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study found that compared with HC group, NSSI group had significantly longer N2, P3a, and P3b latency and significantly lower P3a and P3b amplitude, indicating that patients with depression had lower brain nerve excitability and cognitive speed, suggesting that NSSI group may have cognitive impairment. This is consistent with previous study, as Zhou et al (2022) used oddball paradigm to compare the differences of P3b components among NSSI + MDD, MDD and HC groups. Leone et al (2021) used laser evoked potential as an index to study the suicide risk of NSSI adolescents suggest that the amplitude of N2 component in NSSI patients is reduced, which is different from our study, may be due to different experimental paradigms.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies suggest that N2 represents reaction inhibition and conflict monitoring, P3a is related to automatic attention capture, and P3b is related to stimulus classification and processing, working memory, reaction inhibition and executive function ( Bareš et al, 2007 ; Albert et al, 2010 ; Sanger and Dorjee, 2015 ; Deiber et al, 2021 ; Penengo et al, 2022 ), which seems to explain the results of this study. One study found that the main effect of N2 component was significant under whether self-injury cues were present, and N2 represented conflict detection and monitoring, which may indicate that greater conflicts were generally detected during exposure to self-injury cues ( Zhou et al, 2022 ). Under the self-injury cue, the P3 amplitude of NSSI group was larger than that of HC group, and the P3 amplitude with the self-injury cue was significantly larger than that with the neutral cue, indicating that the neural response of NSSI adolescents changed during exposure to the self-injury cue ( Zhou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the other EEG study concerned addictive perspectives of NSSI. 57 Providing neutral pictures and self-injury-related pictures, researchers used a two-choice Oddball paradigm to examine the neural reactivity of NSSI. The amplitude of P3d, reflecting the process of response inhibition, showed a significant main effect of cue as well as a significant group×cue interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al. ( 2023 ) found that adolescents with major depressive disorder (MDD) with non-suicidal self-injurious behaviors had lower Depression Scale scores and Ottawa Self-Harm Scale scores when treated with selective serotonin reuptake inhibitors (SSRIs) combined with rTMS compared with medication (SSRIs) alone. Impaired behavioral inhibition was improved to a greater extent after iTBS intervention in heroin-addicted patients ( Kang et al.…”
Section: Discussionmentioning
confidence: 99%